Interdisciplinary Environmental Sciences of the Present and Future: Applied Ecology, Integrative Biology, and Integral Ecology - Illescas-Cobos, Abiael Alexis (2025)
This essay analyzes the interrelation between applied ecology, integrative biology, and integral ecology as key disciplines in environmental sciences. It examines their interdisciplinary foundations, similarities, and differences from a reflective perspective, highlighting how their prospects and potential integration can contribute to addressing contemporary environmental challenges. Applied ecology focuses on the practical resolution of environmental problems. Integrative biology delves into the interactions among organisms, their evolution, and their environment. Integral ecology provides a framework to address the interconnections between natural and sociocultural systems. Based on a strategic selection of literature, this essay analyzes these disciplines in their respective contexts to underscore their relevance in research aimed at developing sustainable and holistic solutions to current and future environmental challenges.